Two brothers presented with rare clinical characteristics with a novel LAGE3 variant: a case report and literature review - Jieru Wei; Gongping Zhao; Lijie Li; Cuihua Liu; Jitong Li (BMC Pediatrics)
Abstract Background Variants in the LAGE3 gene can lead to Galloway-Mowat syndrome (GAMOS), a rare genetic disease. Currently, there have been a total of 6 reported cases worldwide, all occurring in children under the age of 3 years old. The main features of LAGE3 variants include early-onset nephrotic syndrome, microcephaly, developmental delay, and neurological abnormalities, with a poor prognosis. However, there are few reports on mild clinical manifestations and prognosis associated with LAGE3 variants. Case presentation Here, we report two brothers, aged 9 and 5 years old respectively, from a family, both presenting with nephrotic syndrome with different types of renal pathology. They both had a high-arched palate and were treated with steroids and tacrolimus, resulting in negative urine protein. Genetic sequencing revealed that both siblings carried a hemizygous variant in the LAGE3 gene: c.389T > G (p.V130G). However, neither of them exhibited the typical features of microcephaly, developmental delay, or neurological abnormalities associated with LAGE3 gene variants. Currently, both siblings have normal renal function and are being regularly followed up with a good prognosis. Conclusions This report is the first to document patients with LAGE3 variants who do not exhibit microcephaly, developmental delay, or neurological abnormalities. Additionally, it is the first case where proteinuria manifested at an older age and had a positive prognosis. The two siblings represent the 7th and 8th cases of children with LAGE3 variants, expanding the genotype and phenotype spectrum of LAGE3 variants, providing new insights for clinical diagnosis and risk assessment.